2022
DOI: 10.5812/gct-126518
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Regression Analysis of Citrus Genotype Under Cold Stress

Abstract: Background: Citrus is among the cold temperature (freezing) susceptible plants. The performance of storage and breeding of horticultural crops is mainly dependent on the correlation among the traits. Objectives: The present study was conducted to identify the physiological and biochemical traits of some citrus cultivars with the greatest influence on stress tolerance and determine the direct and indirect effects of these traits on the median Lethal Time (LT50) using integrated pathway analysis (i.e., stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These results highlight that most parameters were strongly positively correlated, meaning that improvements in one trait can positively and beneficially affect the others. Moreover, a significant and positive correlation between antioxidant activity and MDA levels in different citrus varieties has already been documented in the literature 84 – 86 . Cluster analysis serves as a statistical technique, for grouping the traits or the differentiation of various populations based on a variety of characteristics 87 89 .…”
Section: Discussionmentioning
confidence: 79%
“…These results highlight that most parameters were strongly positively correlated, meaning that improvements in one trait can positively and beneficially affect the others. Moreover, a significant and positive correlation between antioxidant activity and MDA levels in different citrus varieties has already been documented in the literature 84 – 86 . Cluster analysis serves as a statistical technique, for grouping the traits or the differentiation of various populations based on a variety of characteristics 87 89 .…”
Section: Discussionmentioning
confidence: 79%
“…Coefficient of variation and linear regression are used to determine the relationship of linear changes in two variables, and are very important in plant breeding studies 88 . SalehiSardoei et al 89 reported that there is a significant and positive correlation between ion leakage and water core in citrus cultivars. Correlation among attributes may help plant breeding researchers to indirectly select important stress traits through other traits that are easier to measure 90 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the allopolyploid hybrid has lower photoinhibition (Fv/Fm), less oxidative marker accumulation and greater increases in antioxidant activities under cold and light stress relative to its diploid and doubled-diploid parents [33]. Mandarin is the most cold-tolerant citrus type, showing the least significant down-regulation of photosynthetic parameters and highly efficient antioxidant system under natural chilling stress [34], and C. unshiu shows the highest cold tolerance (−8.4 LT50) with a higher chlorophyll content and lower lipid peroxidation compared with C. sinensis, C. paradise, and C. limon [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, plant genotype is the determinant of the potential of cold tolerance, whereas other factors can only modify this potential [23]. According to previous studies of citrus, mandarin is the most cold-tolerant, followed by sweet orange and grapefruit, while lemon and lime are the least cold-tolerant [23,24], and substantial research has indicated that satsuma mandarin (C. unshiu) is the most cold-hardy commercial cultivar [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%